1989
DOI: 10.1182/blood.v74.5.1472.bloodjournal7451472
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and granulocyte-macrophage colony-stimulating factor are candidate growth factors for chronic myelomonocytic leukemia cells

Abstract: Previous studies suggest that malignant cells from some patients with myeloid leukemias produce colony-stimulating factors (CSFs) that can function as autocrine growth factors in vitro. We have examined the roles of interleukin-6 (IL-6) and granulocyte-macrophage CSF (GM-CSF) in the proliferation of myeloid leukemia cells. IL-6 activity was assessed in conditioned medium (CM) from myeloid leukemia cell cultures or cell lysates using IL-6-dependent KD83 and 7TD1 murine cell lines. Media conditioned by cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…We have originally shown that extensive formation of colony-forming units granulocyte/macrophage (CFU-GM) without the addition of exogenous growth factors is an in vitro characteristic of a subgroup of patients with CMML [ 4 ]. This observation has been reproduced by others [ 5 , 6 ] and seems to be an in vitro phenomenon, which is typical for CMML since it can be regularly demonstrated in CMML but is not a common finding in other MPNs including CML. High spontaneous CFU-GM growth (≥100/10 5 MNC) was found in 40% of CMML patients in a small retrospective study including 30 patients [ 7 ].…”
Section: Introductionsupporting
confidence: 80%
“…We have originally shown that extensive formation of colony-forming units granulocyte/macrophage (CFU-GM) without the addition of exogenous growth factors is an in vitro characteristic of a subgroup of patients with CMML [ 4 ]. This observation has been reproduced by others [ 5 , 6 ] and seems to be an in vitro phenomenon, which is typical for CMML since it can be regularly demonstrated in CMML but is not a common finding in other MPNs including CML. High spontaneous CFU-GM growth (≥100/10 5 MNC) was found in 40% of CMML patients in a small retrospective study including 30 patients [ 7 ].…”
Section: Introductionsupporting
confidence: 80%
“…GM-CSF, M-CSF and G-CSF in murine MPSV-induced myeloproliferative syndrome (Le Bousse-Kerdilgs et al, 1992) as well as elevated serum M-CSF levels in patients with MPD (Gilbert et al 1989). There have also been data suggesting that IL6 and GM-CSF act as autocrine growth factors for chronic myelomonocytic leukaemia cells under in vitro conditions (Everson et al, 1989). Therefore, two questions can be asked: are these cytokines responsible for the spontaneous colony formation of megakaryocyte progenitors in MPD, and is there an autonomous production of these growth factors in MPD?…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the discovery of the colony‐forming precursor cells, a typical in vitro growth pattern in juvenile myelomonocytic leukemia (JMML) (3–5) and also in adult CMML (6, 7) were recognized. A fundamental biological characteristic of JMML and CMML is hypersensitivity of colony‐forming precursor cells to hematopoietic growth factors (8, 9) causing abundant cytokine independent formation of myeloid colonies, while growth of BFU‐E is decreased, resulting in an abnormally low E : M ratio. These abnormalities are more prominent in cultures from PB than from BM (3).…”
Section: Discussionmentioning
confidence: 99%